千年桐优良种质资源筛选与综合评价"Screening and comprehensive evaluation of excellent germplasm resources of Aleurites montana" - 曹杰1，米小琴2，熊波3，黄会猛2，许剑萍3，高凌2，曾传圣3，陈刚3CAO Jie1，MI Xiaoqin2，XIONG Bo3，HUANG Huimeng2，XU Jianping3，GAO Ling2，ZENG Chuansheng3，CHEN Gang3 (Zhongguo youzhi)
旨在为千年桐产业良种化提供科学依据，以经筛选的29份千年桐优良母株为试验对象，测量其树体表型性状（树高、冠幅和胸径）、果实表型性状（30个鲜果质量、30个干果质量、单株鲜果总质量和干籽出仁率）及油脂性状（干仁含油率，油酸、亚油酸、α-桐酸含量和α-桐酸/β-桐酸），并对各性状指标进行相关性分析、聚类分析和主成分分析，分析评选出优良种质资源。结果表明：29份千年桐的12个性状变异系数介于10.82%~45.84%，其中单株鲜果总质量变异最大；遗传多样性指数介于1.46~1.97；相关性分析表明30个鲜果质量与树高、冠幅呈显著正相关，单株鲜果总质量与胸径呈极显著正相关，干仁含油率与干籽出仁率呈显著正相关，与单株鲜果总质量呈极显著正相关，油酸与亚油酸呈显著正相关，α-桐酸与油酸呈极显著负相关，与α-桐酸/β-桐酸呈极显著正相关；通过聚类分析可将千年桐优良母株划分为3个类群，类群Ⅱ中的种质具有筛选树体矮化、高产、高含油率良种的潜力；通过综合指标与经济指标主成分分析，筛选出AF-7和YZQ-6为最优母株。综上，初步构建了千年桐种质资源综合评价体系，AF-7和YZQ-6可作为今后千年桐良种选育的母株。 Aiming to provide a scientific basis for the seeding of A. montana industry， 29 excellent maternal plants of A. montana selected as the experimental subjects,the plants phenotypic traits（tree height, crown width and diameter at breast height）, fruit phenotypic traits(30 fresh fruit mass, 30 dry fruit mass, total mass of fresh fruits per plant and kernel yield of dry seeds), and oil traits(oil content of dry kernel, oleic acid , linoleic acid, α-eleostearic acid and α-eleostearic acid/β-eleostearic acid) of A. montana were determined.Correlation analysis, cluster analysis and principal component analysis were also carried out for each trait index to analyze and select the excellent germplasm resources. The results showed that the coefficient of variation for 12 traits of 29 A. montana ranged from 10.82% to 4584% with the maximum variation in total mass of fresh fruits per plant.The genetic diversity index was between 1.46 and 1.97. Correlation analysis showed that 30 fresh fruit mass was significantly and positively correlated with tree height and crown width, total mass of fresh fruits per plant was highly significantly and positively correlated with diameter at breast height, the oil content of dry kernel was significantly and positively correlated with the kernel yield of dry seeds, and highly significantly and positively correlated with total mass of fresh fruits per plant, oleic acid was significantly and positively correlated with linoleic acid, and α-eleostearic acid was highly significantly and negatively correlated with oleic acid, and highly significantly and positively correlated with α-eleostearic acid/β-eleostearic acid. The excellent maternal plants of A. montana could be divided into three groups by cluster analysis,and the germplasm in group Ⅱ had the potential to screen for tree dwarfing, high yield, and high oil content varieties. AF-7 and YZQ-6 were selected as the optimal maternal plants by principal component analysis of comprehensive and economic indicators. In summary, A comprehensive evaluation system for A. montana germplasm resource is preliminarily constructed, and AF-7 and YZQ-6 can be used as the maternal plants for the future selection of excellent varieties of A. montana.